MAKNA PENDERITAAN YESUS: Uraian Eksegetis dan Refleksi Teologis MRK 15:33-39 - Stanislaus, Surip; Lam, Tran Ngoc (UNIKA Santo Thomas, 2025)
Suffering is an essential part of human nature. Suffering appears in all forms, from physical, and psychological to spiritual. What causes it and what does it mean? Human history offers a variety of answers, but no single answer is satisfactory. The definitive and perfect answer can only be found in Jesus Christ, the Son of God who became human and suffered, was crucified, and died on the cross. The answer will be presented through exegetical description and theological reflection on Mrk 15:33-39 using library research methods. The crucified Jesus is depicted in real terms through terrible suffering, feelings of abandonment from God the Father, and the voluntary surrender of His life. The climax of Jesus’ suffering was expressed in His cry, “My God, My God, why hast Thou forsaken Me?” (Mrk 15:34). Quoting the prayer of the righteous suffering man in Ps 22:2, a seemingly desperate cry becomes a cry of confidence in God’s coming presence and glorification. By voluntarily entering into the greatest suffering, Jesus revealed the true meaning of suffering and became the hope for all human beings experiencing suffering in their lives. As an innocent Servant of God the Father, He willingly endured human suffering, in order to enable humans to share in His salvific suffering. By entering into the mystery of the suffering of Jesus Christ, humanity discovers the true meaning of suffering. Through the Sacrament of Anointing of the Sick, those who are sick and suffering are united with Jesus so that they can also obtain His liberation and glorification. Imitating Jesus’ attitude of voluntarily accepting suffering can free a person from the influence and impact of suffering itself. Inner freedom based on trust, hope, and love for God not only enables a person to endure life’s suffering patiently but also turns it into something good and useful for himself/herself and others. Saint Francis of Assisi is obvious evidence when he actually found joy in all suffering with a holy desire, namely to feel as much suffering as possible as well as the love of Christ.